To Know and Be Known: An Intimacy-Based Explanation for the Gender Gap in Biblical Literalism - Kent, Blake Victor (Journal for the scientific study of religion, 2019)
We assess the gender gap in U.S. Christianity by examining in a national sample (Baylor Religion Survey 2010) a particularly robust measure of religiosity: biblical literalism. Women are more likely to report biblical literalism than men in bivariate comparisons, but we argue that intimate attachment to God is a related intervening mechanism. The results of this study indicate: (1) intimate attachment to God is associated with more literal views of the Bible, (2) after accounting for attachment to God women are no longer associated with increased literalism, (3) divine proximity-seeking behaviors are associated with more literal views of the Bible, (4) proximity-seeking moderates the relationship between attachment to God and Bible views, and (5) gender moderates the relationship between both attachment to God and proximity-seeking behaviors and Bible views. The evidence presented here provides a plausible mechanism by which gender differences in biblical literalism may be accounted for.